The Level of Sustainability Assurance: The Effects of Brand Reputation and Industry Specialisation of Assurance Providers - Martínez-Ferrero, Jennifer (Journal of business ethics, 2018)
This research focuses on examining the relationship between some attributes of assurance providers and the level of sustainability assurance. By using the propensity to issue negative conclusions in the assurance statement as an indicator of the level of assurance, we examine whether the brand name and industry specialisation of the practitioners have an impact on the assurance opinion issued. Using an international sample of 1233 firm-year observations over the period 2007–2014, the findings document the impact of the brand reputation and industry specialisation of assurance providers on the level of assurance. The probability of detecting material errors and omissions in a sustainability report is higher if it is verified by a Big 4 auditing firm and by an industry expert as an assurance practitioner. The greater experience in providing audit services and the relevant skills and training provided by Big 4 firms, as well as the greater knowledge and experience of industry experts, increase the propensity to report more accurate opinions about a sustainability report. The findings are robust for alternative measures for the level of assurance and the industry specialisation.